KETERBUKAAN INFORMASI PUBLIK PEMERINTAH PROVINSI KALIMANTAN TIMUR - Sri Rezeki Marietha (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aims to describe and analyze how implementation of the implementation of Act Law Number 14 Year 2008 in East Kalimantan Provincial Government as well as describe the supporting and inhibiting factors faced in the implementation of information disclosure. This type of descriptive research with qualitative approach. Analysis of data used is interactive model. The result of research looked the succesful implemention of public information disclosure is supported by the Provincial. Regulation of East Kalimantan Province No. 15 of 2012 so that the workflow of information services becomes more clear. The high commitment of the Governor as the Head of Region as well as the communication that has been running smoothly and the social and political environment has also been a supporter of the success of policy implementation in the Government of East Kalimantan.Keywords: implementation, information disclosure, public information service